Women's reproductive traits and cerebral small-vessel disease: A two-sample Mendelian randomization study - Wang, Zhenqian; Lu, Jiawen; Weng, Weipin; Zhang, Jie (Frontiers in Neurology, 2023)
Background Observational studies have suggested that women's reproductive factors (age at menarche (AAM), age at first birth (AFB), age at first sexual intercourse (AFS), age at natural menopause (ANM), and pregnancy loss) may influence the risk of cerebral small-vessel disease (CSVD) although the causality remains unclear. Methods We conducted two-sample univariable Mendelian randomization (UVMR) and multivariable MR (MVMR) to simultaneously investigate the causal relationships between five women's reproductive traits and CSVD clinical [intracerebral hemorrhage (ICH) by location or small-vessel ischemic stroke (SVS)] and subclinical measures [white matter hyperintensities (WMH), fractional anisotropy (FA), and mean diffusivity (MD)], utilizing data from large-scale genome-wide association studies of European ancestry. For both UVMR and MVMR, the inverse-variance-weighted (IVW) estimates were reported as the main results. The MR-Egger, weighted median, generalized summary-data-based MR (GSMR), and MR-pleiotropy residual sum and outlier (MR-PRESSO) methods for UVMR and MVMR-Egger, and the MVMR-robust methods for MVMR were used as sensitivity analyses. Sex-combined instruments for AFS and AFB were used to assess the impact of sex instrumental heterogeneity. Positive control analysis was implemented to measure the efficacy of selected genetic instruments. Results We found no evidence to support causal associations between genetic liability for women's reproductive factors and the risk of CSVD in UVMR (all P-values > 0.05). Using MVMR, the results were consistent with the findings of UVMR after accounting for body mass index and educational attainment (all P-values > 0.05). Sensitivity analyses also provided consistent results. The putative positive causality was observed between AAM, ANM, and ovarian cancer, ensuring the efficacy of selected genetic instruments. Conclusion Our findings do not convincingly support a causal effect of women's reproductive factors on CSVD. Future studies are warranted to investigate specific estrogen-related physiological changes in women, which may inform current researchers on the causal mechanisms involved in cerebral small-vessel disease progression.